Adrift in the gray zone: IRB perspectives on research in the learning health system. Issue 2 (2nd April 2016) - Lee, Sandra Soo-Jin; Kelley, Maureen; Cho, Mildred K.; Kraft, Stephanie Alessi; James, Cyan; Constantine, Melissa; Meyer, Adrienne N.; Diekema, Douglas; Capron, Alexander M.; Wilfond, Benjamin S.; Magnus, David
ABSTRACT: Background: Human subjects protection in health care contexts rests on the premise that a principled boundary distinguishes clinical research and clinical practice. However, growing use of evidence-based clinical practices by health systems makes it increasingly difficult to disentangle research from a wide range of clinical activities that are sometimes called "research on medical practice" (ROMP), including quality improvement activities and comparative effectiveness research. The recent growth of ROMP activities has created an ethical and regulatory gray zone with significant implications for the oversight of human subjects research.Methods: We conducted six semistructured, open-ended focus-group discussions with institutional review board (IRB) members to understand their experiences and perspectives on ethical oversight of ROMP, including randomization of patients to standard treatments.Results: Our study revealed that IRB members are unclear or divided on the central questions at stake in the current policy debate over ethical oversight of ROMP: IRB members struggle to make a clear distinction between clinical research and medical practice improvement, lack consensus on when ROMP requires IRB review and oversight, and are uncertain about what constitutes incremental risk when patients are randomized to different treatments, any of which may be offered in usual care. They characterized the central challenge as a balancing act between, on the one hand, making information fully transparent to patients and providing adequate oversight, and on the other hand, avoiding a chilling effect on the research process or harming the physician–patient relationship.Conclusions: Evidence-based guidance that supports IRB members in providing adequate and effective oversight of ROMP without impeding the research process or harming the physician–patient relationship is necessary to realize the full benefits of the learning health system.